Atrial fibrillation per se was a major determinant of global left ventricular longitudinal systolic strain. Issue 26 (June 2016) - Lee, Hung-Hao; Lee, Meng-Kuang; Lee, Wen-Hsien; Hsu, Po-Chao; Chu, Chun-Yuan; Lee, Chee-Siong; Lin, Tsung-Hsien; Voon, Wen-Chol; Lai, Wen-Ter; Sheu, Sheng-Hsiung; Su, Ho-Ming
Abstract : Abstract: Atrial fibrillation (AF) may cause systolic abnormality via inadequate diastolic filling and tachycardia-induced cardiomyopathy. Global longitudinal strain (GLS) is a very sensitive method for detecting subtle left ventricular systolic dysfunction. Hence, this study aimed to evaluate whether AF patients had a more impaired GLS, AF was a major determinant of GLS, and determine the major correlates of GLS in AF patients. The study included 137 patients with persistent AF and left ventricular ejection fraction (LVEF) above 50% and 137 non-AF patients matched according to age, gender, and LVEF. Comprehensive echocardiography with GLS assessment was performed for all cases. Compared with non-AF patients, AF patients had a more impaired GLS, a larger left atrial volume index, higher transmitral E wave velocity (E), and early diastolic mitral velocity (Ea) (all P  < 0.001) but comparable E/Ea. After adjustment for baseline and echocardiographic characteristics, the presence of AF remained significantly associated with impaired GLS (β = 0.533, P  < 0.001). In addition, multivariate analysis of AF patients indicated that faster heart rates and decreased E, Ea, and LVEF were associated with more impaired GLS. This study demonstrated that AF patients had a more impaired GLS than non-AF patients, although LVEF was comparable between the 2 groups. AF was a major determinant of GLS even after adjustment for relevant clinical and echocardiographic parameters.